Intravenous administration of iron dextran as a potential inducer for hemochromatosis: Development of an iron overload animal model - Khristian, Erick; Ghozali, Mohammad; Bashari, Muhammad H.; Purnama, Jeri N.; Irianto, Gunawan; Panigoro, Ramdan; Safitri, Ratu (Narra J, 2024)
Iron overload in transfusion-dependent thalassemia patients represents a significant public health challenge due to its high mortality rate and risks of severe complications. Therefore, developing safe and effective therapeutic modalities for managing iron overload is critical, as current animal models inadequately replicate human conditions. The aim of this study was to investigate the effects of intravenous iron dextran on hepatocyte morphology, liver iron concentration, and serum iron profile changes as a model for hemochromatosis. An experimental design with a post-test-only control group method was conducted using animal models. Fifty rats were used and divided into ten groups, nine received different intravenous doses of iron dextran: 10, 20, 30, 40, 50, 60, 80, 100, and 120 mg/kg body weight (BW) and a control group received no treatment. The results showed that intravenous iron dextran starting at a dose of 10 mg/kg BW caused significant changes in liver iron concentration while starting at 20 mg/kg BW significantly affected hepatocyte morphology, transferrin levels, unsaturated iron binding capacity, serum iron levels, and transferrin saturation. Intravenous iron dextran starting at 40 mg/kg BW resulted significant changes in the level of total iron binding capacity compared to control group. In conclusion, intravenous iron dextran significantly altered hepatocyte morphology, increased liver iron concentration, and modified the serum iron profile, reflecting changes that might be observed in patients with transfusion-dependent thalassemia.